Hesbollah Kuranji at the Front Padang Area (1945-1948) - Handayani, Revi (Islam Transformatif : Journal of Islamic Studies, 2021)
Abstract This paper examines the struggle of the militant ranks Hezbollah at the Front Padang Area. Most of the literature written only talks about the role of regular soldiers (official soldiers recruited by the government) who often fight in the front lines, even though the activation of the militias also contributed the most significant contribution to the struggle at that time physical revolution. The Hezbollah written in this article is Hezbollah in the Padang Region, especially those who are members of the Padang City Hezbollah, who are aware of the existing situation and conditions, so they are persistently trying to reclaim their homeland from the colonial powers of the Allies and the Dutch who want to re-establish their power. The research method in this paper is the historical method, which critically examines and analyzes records and relics. The research steps consist of four stages: Heuristics, Criticism, Interpretation and Historiography. In collecting data and research materials, both historical actors and witnesses were used, apart from using literature and documentary studies and interviews with sources. The result of this research is that the struggle of the Hezbollah Army (Lasykar) of Padang City is based on the intention of "Jihad FiiSabillilah" to struggle to uphold the State and Religion solely for the sake of Allah, only with great encouragement and very simple motivation. However, the principle cannot be separated from any political influence. Hezbollah army has a firm stance that all disturbances and disturbances to public order that occur in the city of Padang are the responsibility of all levels of society in the city of Padang. Keywords: Hezbollah army, Corporal Revolution, Front of Padang Area Â Abstrak TulisanÂ ini mengkaji tentang perjuangan barisan kelaskaran Hizbullah di Front Padang Area. Selama ini literatur mengenai barisanÂ perjuangan yang banyak ditulis hanya peranan tentara reguler (tentara resmi yang direkrut pemerintah) saja yang sering berjuang dibarisan depan, padahal aktivasi dari barisan kelaskaran juga memberikan sumbangan terbesar dalam perjuangan pada masa revolusi fisik. Hizbullah yang ditulisÂ dalam artikel iniÂ adalah HizbullahÂ di Daerah Padang, khususnyaÂ yangÂ tergabungÂ dalamÂ Hizbullah Kota PadangÂ telahÂ sadarÂ terhadapÂ situasiÂ danÂ kondisi yang ada, sehingga dengan gigih mereka berusaha merebut kembali tanah airnya dari kekuasaan penjajahanÂ SekutuÂ danÂ BelandaÂ yangÂ inginÂ menancapkanÂ kembali kekuasaanya. Metode Penelitian dalam tulisan ini adalah MetodeÂ Historis,Â yaitu proses menguji dan menganalisis secara kritis rekaman dan peningalan masa lampau. Adapun langkah-langkah penelitian terdiri dari empat tahap, yaitu: Heuristik,Â Kritik, Interpretasi dan Historiografi. Dalam mengumpulkan data dan bahan penelitian, selain mengunakan studi literatur dan dokumenter, digunakan pula wawancara terhadap narasumber, baik pelaku dan saksi sejarah. Hasil Penelitian ini adalah Perjuangan Lasykar Hizbullah Kota Padang tersebut dilandasi niat â€œJihad Fii Sabillilahâ€ berjuang menegakan Negara dan Agama semata-mata hanya karena Allah, Hanya dengan dorongan semangat yang besar serta motivasi yang sangat sederhana namun prinsipnya tidak terlepas dari pengaruh politik manapun, Lasykar Hizbullah ini mempunyaiÂ ketegasanÂ pendirianÂ bahwaÂ segalaÂ kekacauanÂ danÂ ganguan terhadapÂ ketertibanÂ masyarakatÂ yang terjadi di Kota Padang adalah tangung jawab semua lapisan masyarakat yang berada di Kota Padang. Kata Kunci: Lasykar Hizbullah, Revolusi Fisik, Front Padang Area